Intersectional gender perspective in the sentences from the Inter-American Court of Human Rights - Brevis Cartes, Priscilla; Bustos Ibarra, Cecilia; Gauché Marchetti, Ximena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this paper the development of intersectionality as a concept present in the process of judging with gender perspective is analyzed, particularly its impact on the case-law of the Inter-American Court of Human Rights (I/A Court HR). The methodology is qualitative, mainly review of sentences from the I/A Court HR. 13 sentences from 2015 to 2022 were selected. It is concluded that the I/A Court HR has increasingly incorporated and used the intersectional perspective as an analytical category to study, understand and confront the discriminations that become an aggravated form of discrimination and barriers to access to justice.